To determine which example correctly demonstrates polynomial subtraction, we need to perform the subtraction \((2x^2 + 6x + 1) - (3x^2 + 3x + 9)\).
Let's go through the steps of the subtraction:
-
Distribute the negative sign across the second polynomial: \[ (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = 2x^2 + 6x + 1 - 3x^2 - 3x - 9 \]
-
Combine like terms:
- For \(x^2\) terms: \(2x^2 - 3x^2 = -x^2\)
- For \(x\) terms: \(6x - 3x = 3x\)
- For constant terms: \(1 - 9 = -8\)
Thus, the result is: \[ -x^2 + 3x - 8 \]
Now, let's see which of the responses matches this result:
- \((2x^2 + 6x + 1) - (3x^2 + 3x + 9) = -5x^2 + 3x - 8\) → Incorrect.
- \((2x^2 + 6x + 1) - (3x^2 + 3x + 9) = x^2 + 3x + 8\) → Incorrect.
- \((2x^2 + 6x + 1) - (3x^2 + 3x + 9) = -x^2 + 3x - 8\) → Correct.
- \((2x^2 + 6x + 1) - (3x^2 + 3x + 9) = 5x^2 + 9x + 10\) → Incorrect.
The correct choice is: \[ (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = -x^2 + 3x - 8 \]